Hydrogen peroxide ativeness efficincy against wart and globoderosis of potato - Zelya, A.; Makar, T.; Zelya, G. (Quarantine and plant protection, 2024)
Goal. The preparation’s efficiency Peroxide urea, crystal powder, (complex urea chemical combination, 65%: hydrogen peroxide, 35%) determined on potato wart zoosporangium causative agents Synchytrium endobioticum (Schilb.) Perc. and cysts potato yellow cyst nematodes Globodera rostochiensis (Wollenweber). Methods. Laboratory (to conduct laboratory trials for determining Peroxide urea (UHP) against wart causative agents and potato globoderosis), field trials (determining preparation’s efficiency against present diseases causative agents in field trials), plant pathological (diseases’ causative agents determining and identification), mathematical statistical (researches’ results treating). Technical efficiency determined as per «Testing technique and pesticide usage», (S. Trybel, D. Sygaryova, M. Sekun, etc). Researches conducted on sensitive to wart and globoderosis potato variety Poliska rozheva. Results. Peroxide urea efficiency action against potato wart causative agent S. Endobioticum at norm rate 50—150 kg/ha varied in scope 53.2—78.3%. UHP preparation efficiency against globoderosis consisted of 71.4—81.9%. This disease caused by G. rostochiensis, it depends upon preparation norm rate. Conclusions. UHP usage at norm rate 50—150 kg/ha favored decrease the viable zoosporangium potato wart causative agents number from 58 to 24 in 1 g of soil. Active efficiency consisted of 53.2—78.3%. It’s efficiency was on level 71.4—81.9% against yellow potato cyst nematode. The cyst quantity of G. rostochiensis decreased from 120 to 14 in 100 cm3of soil. UHP allows to decrease the density ofwart causative agents and globoderosis (G. rostochiensis) in soil. So this preparation recommends for these diseases’ control in spread source.